Smoking and drinking behavior, knowledge, and attitudes among urban and rural public-school students in Efate Island, Vanuatu: a comparative study - Emi Nakaseko; Sayaka Kotera; Minato Nakazawa (BMC, 2022)
Abstract Background Underage smoking and drinking are public health issues in Vanuatu. This study aims to describe the behavior, knowledge, attitudes, and perceptions of parents, siblings, and peers regarding smoking and drinking among urban and rural public-school students in Vanuatu. Methods This cross-sectional study included 358 students (urban, 217; rural, 141; aged 12-14 years) from the public schools in Efate Island, Vanuatu. Data were collected using self-administered questionnaires. Chi-square and Mann-Whitney U tests were used to determine the rural-urban differences. Results Urban students showed a higher prevalence of ever smoking (13.5%), ever drinking (16.9%), intention to smoke (11.1%), and intention to drink (14.0%) compared to rural students (10.3%, 8.3%, 5.8%, and 9.5%, respectively); although a significant difference was only observed in the prevalence of ever drinking. Urban students were more likely to be aware of the health hazards of substance use and showed higher self-efficacy to refuse tobacco and alcohol compared to rural students. Parents in rural areas were less likely to talk about the health hazards of substance use with their children and were more likely to offer tobacco or alcohol to them compared to parents in urban areas. Conclusions The results provide evidence of rural-urban differences in the behavior, attitude, knowledge, and perceptions of parental behavior regarding smoking and drinking. The findings suggest that issues related to underage smoking and drinking differ between urban and rural students. Future intervention programs for reducing underage smoking and drinking should be adapted in recognition of urban and rural differences.